Migrant networks as substitute for institutions: Evidence from Swiss trade - Pierre-Louis Vézina (Graduate Institute of International and Development Studies, 2010)
This paper uses an untapped dataset on Swiss immigration and a novel instrumental variable to test three channels through which migrants promote trade. The main finding is that migrant networks are an effective substitute for formal institutions in facilitating trade. The effect takes place entirely on the extensive margin, suggesting migrant networks may be reducing fixed entry costs characterized by corruption.
Keywords: F22; F14; D73; D8; 330; trade; migration; corruption; Migranten; Soziales Netzwerk; Handelseffekt; Einwanderung; Schweiz